Exploiting code mobility for dynamic binary obfuscation - Falcarin, Paolo; Di Carlo, Stefano; Cabutto, Alessandro; Garazzino, Nicola; Barberis, Davide (2011 World Congress on Internet Security, 2011)
Software protection aims at protecting the integrity of software applications deployed on un-trusted hosts and being subject to illegal analysis. Within an un-trusted environment a possibly malicious user has complete access to system resources and tools in order to analyze and tamper with the application code. To address this research problem, we propose a novel binary obfuscation approach based on the deployment of an incomplete application whose code arrives from a trusted network entity as a flow of mobile code blocks which are arranged in memory with a different customized memory layout. This paper presents our approach to contrast reverse engineering by defeating static and dynamic analysis, and discusses its effectiveness.